Ecología de la reproducción de la paloma Zenaida auriculata. 1. Variaciones estacionales en peso corporal, gonadas, reservas de lipidos y muda - Bucher, Enrique H.; Gómez, Eduardo; di Tada, Ismael E.; Reati, Gustavo J. (Ecosur, 2025)
The seasonal cycle of Zenaida auriculata chrysauchenia was studied in Córdoba, Argentina (31° S), where the bird has become a serious agricultural pest. Monthly samples were obtained from June 1970 to November 1972. / total of 3,650individuáis was analysed. Body weight was on average heavier in winter (May-October) than in summer and autumn (Novetmber-Aprill. Males were about Solo heavier than females throughout the year, and juvenile were lighter than adults. Significant differences in weight were found between localities, being related to the proportion of cultivated land in each area. On the average, males had an annual cycle in gonad weight showing a mínimum from May to July, but males producing sperm were found throughout the year. There was no demonstrable cycle in females. Significant differences in testis weight between localities were also found. Apparently, abundance of food and photoperiodic changes to a lesser degree, are involved in the regulation of the sexual cycle. Body fat reserves tended to be higher in winter. The proportion of birds showing fat accumulation raised to a peak in May 1972 (83 o/o), following a extremely poor rainy season. At the same time part of the colonies deserted the area, indicating that a migratory or nomadic process was involved. Moulting season extends on average from Octobcr to July, but great variation occurs. Among the birds showing crop gland milk production, the proportion of those with growing primarios was significantly less than in the rest, suggesting that moult can be arrested fot breeding. Double moult was recprded in ten individuáis. Similarities between the annual cycle of Zenaida auriculata and those of severa! arid land pigeons of Australia and Africa are discussed.